Pelatihan Pewara Bahasa Jawa untuk Meningkatkan Keberanian Berkomuniasi di Depan Masyarakat pada Kelompok Sanggar Seni Larasati Kecamatan Padamara - Andriyan Verrysaputro, Exwan; Fuaddah, Ashlikhatul; Riksaning Ayu, Kilau (COVIT (Community Service of Tambusai), 2023)
Language is the most effective communication tool. Every human being uses language to interact with other humans. To achieve good communication, good language mastery is also needed. Good language is communicative language that is often used in oral communication. Not infrequently, many people still do not have the courage to express their opinions in public. So efforts are needed to increase people's courage to speak in public. The aim of this service is to increase people's courage to speak in public. In order to achieve this goal, various methods are used, including lectures, demonstrations, questions and answers, direct practice, and assignments. At the end of the program an assessment is carried out to see the level of success of the program. The posttest results showed that there was an increase in participants' courage in speaking in public by 51%, from an average pretest score of 44 to 85. This 36% increase is considered a fairly high increase. Keywords: Anchor; Javanese language; Communication.